Cancer Care of Children, Adolescents and Adults With Autism Spectrum Disorders: Key Information and Strategies for Oncology Teams - Vuattoux, Delphine; Colomer-Lahiguera, Sara; Fernandez, Pierre-Alain; Jequier Gygax, Marine; Choucair, Marie-Louise; Beck-Popovic, Maja; Diezi, Manuel; Manificat, Sabine; Latifyan, Sofiya; Ramelet, Anne-Sylvie; Eicher, Manuela; Chabane, Nadia; et al. (Frontiers in Oncology, 2021)
Delivering optimal cancer care to children, adolescents and adults with ASD has recently become a healthcare priority and represents a major challenge for all providers involved. In this review, and after consideration of the available evidence, we concisely deliver key information on this heterogenous group of neurodevelopmental disorders, as well as recommendations and concrete tools for the enhanced oncological care of this vulnerable population of patients.